2008
DOI: 10.1111/j.1540-8191.2008.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Cardiac Biochemical and Inflammatory Markers in Patients on Cardiopulmonary Bypass Undergoing Coronary Artery Bypass Grafting

Abstract: Monitoring of these markers could help to determine implementation of protective interventions during CABG with CPB to prevent myocardial deterioration and to predict the risk and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
2
15
0
1
Order By: Relevance
“…Peak levels of this interleukin is observed in these first hours of the postoperative period, as found by our team in a previous study [6] and by others [16,17]. The presence of hyperthermia in the criteria used avoids the potential confounding effect of vasoactive drugs on the associated hyperdynamic state.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Peak levels of this interleukin is observed in these first hours of the postoperative period, as found by our team in a previous study [6] and by others [16,17]. The presence of hyperthermia in the criteria used avoids the potential confounding effect of vasoactive drugs on the associated hyperdynamic state.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to the feed-back between the release of inflammatory markers and fibrinolysis, other components must be considered in the release of these markers. After CPB (Figure 2) we observed a clear increase in the levels of IL-6 and other interleukins, which interact with each other [16,17] and are involved in producing fever ("postperfusion syndrome") [22]. Also, oxidative stress induced by norepinephrine may release IL-6 in other settings [23].…”
Section: Discussionmentioning
confidence: 99%
“…The average lactate was initially 0.83 ± 0.28 mmol/l on induction for surgery, 0.87 ± 0.33 a half hour from induction, 2.84 ± 1.68 after a quarter of an hour on cardio-pulmonary bypass, 3.48 ± 2.23 at the end of cardio-pulmonary bypass, 4.28 ± 2.48 at the end of surgery, and 4.33 ± 2.56 during ICU admission. A similar study by Meng et al [22] measured lactate and other inflammatory markers in patients undergoing on-pump CABG every 6 h for 24 h after the start of cardio-pulmonary bypass. The lactate was recorded as follows: T0 (1.12 ± 1 mmol/l), T1 (1.15 ± 0.07), T2 (3.12 ± 0.21), T3 (2.97 ± 0.18), T4 (2.58 ± 0.25).…”
Section: Discussionmentioning
confidence: 97%
“…This is further aggravated by the post-operative increased oxygen demand, low output cardiac state, and use of vasoactive agents. This cascade of events can inflect visceral organ injury manifesting in a recognized pattern of liver, kidney, and pancreas biomarker surge within the first 2–3 days after surgery [20–22]. …”
Section: Discussionmentioning
confidence: 99%
“…Plasma interleukin (IL)-6 may play an important role in the development of SIRS [8]. Research has found that IL-6 level are significantly elevated one hour after initiation of CPB and peaks at six hours [9]. Surgical trauma, abnormal shear stress, ischemia, reperfusion, and hypothermia can activate the secretion of IL-6, which can remain elevated after surgery [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%